Heavy metal contamination of topsoil around a cement factory – A case study of Obajana Cement Plc. Issue 1 (31st December 2022) - Akpambang, Victoria Omolara Enobong; Ebuzeme, Gloria Chiogo; Akinola, Joshua Oluwatobi
ABSTRACT: The concentration of heavy metals (Cd, Co, Cr, Pb and Ni) in topsoil samples around Obajana Cement Plc was determined to assess the impact of cement dust emitted from the factory environment. The analysis was carried out using Atomic Absorption Spectrophotometer. Samples of the topsoil were collected from the factory at various distance points. The control was collected from a sparsely populated area which is 15 km away from the factory. The pH of the soils ranges from 6.18 to 8.43 against a controlled pH of 6.11. The EC level decreases with increasing distances from the factory. The soils of all the studied sites have very low silt content and a high sand content. There was significant decrease in Cr, Cu and Cd with an increase in the distance from the cement factory. The concentrations of the metals at each point were below the WHO standard of the individual metal in the soil.